Art as a Mechanism for Enhancing Social Accessibility - Nakagawa, Shin (Journal of Urban Culture Research, 2014)
“Art Access and Advocacy,” the theme of Urban Research Plaza’s 11th international forum, implies the development of access channels through the arts, which enable the participation of socially disadvantaged persons in social activities and ultimately result in the making of a highly communal society. In this article, I will discuss the social context from which this theme emerged. In addition, I will consider the importance of arts management in a few concrete examples.